Evolution and prognostic implications of cardiac damage in women after transcatheter aortic valve implantation - Myagmardorj, Rinchyenkhand; Fortuni, Federico; Galloo, Xavier; Nabeta, Takeru; Meucci, Maria Chiara; Butcher, Steele C.; van der Kley; Frank; Ajmone Marsan, Nina; Bax, Jeroen J. (Springer Nature, 2025)
Recently, a cardiac damage staging system has been proposed in patients with severe AS to improve risk stratification, but there is still paucity of data in women. Accordingly, we aimed to characterize the change in cardiac damage after transcatheter aortic valve implantation (TAVI), and to assess the prognostic value of cardiac damage staging in women. A total of 334 women (mean age 81 +/- 7 years) with severe AS undergoing TAVI were included and retrospectively analyzed. Echocardiography was performed before and 6 months after TAVI. Patients were classified according to the following stages of cardiac damage: 0 = no damage; 1 = left ventricular damage; 2 = left atrial or mitral valve damage; 3 = pulmonary vasculature or tricuspid valve damage; and 4 = right ventricular damage. The primary endpoint was all-cause mortality. Most patients presented with advanced heart failure symptoms (62% in NYHA III-IV). TAVI consistently improved cardiac damage of at least one stage in 43% of patients at 6-month follow-up. During a median follow-up of 48 months, 79 patients (24%) died. Each increment of both baseline (HR per 1-stage increment 1.537, P = 0.001) and follow-up (HR per 1-stage increment 1.714, P = 0.01) cardiac damage stage were independently associated with all-cause death. Moreover, the re-assessment of cardiac damage at 6-month follow-up provided incremental prognostic value over baseline assessment (Chi-square change = 6.885; P = 0.009). TAVI has a beneficial effect on cardiac function and remodeling in women. Cardiac damage assessed before and 6 months after TAVI showed to be consistently and independently associated with prognosis.